MISCELLANEOUS SOUTH EAST ASIAN CUCURBIT NEWS - De Wilde, W.J.J.O. -; Duyfjes, Brigitta E. E. (REINWARDTIA, 2008)
DE WILDE, W.J.J.O. & DUYFES, B.E.E. 2008. Miscellaneous South East Asian cucurbit news. Reinwardtia 12(4):267 â 274. ââ This paper contains corrections, additions, and name changes in several genera, which became apparent since previous publications by the authors in these genera.(1) Baijiania A.M. Lu & J.Q. Li: a range-extension(2) Benincasa Savi: a name change(3) Diplocyclos (Endl.) T. Post & Kuntze: lectotypification of the synonym Ilocania pedata Merr.(4) Gymnopetalum Arn.: a name change, designation of two neotypes, a new record(5) Hodgsonia Hook. f. & Thomson: a new subspecies(6) Indomelothria W.J. de Wilde & Duyfjes: the largest fruits(7) Trichosanthes L.: three new varieties, a name change, amendments of fruit descriptionss, and a range-extension(8) Zehneria Endl.: a new species from Mindanao.